2016
DOI: 10.18172/cig.2918
|View full text |Cite
|
Sign up to set email alerts
|

Modernization of new irrigated lands in a scenario of increasing water scarcity: from large reservoirs to small ponds

Abstract: ABSTRACT. Large rainfed, dryland areas were transformed into irrigated land in northeast Spain

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 54 publications
0
10
0
1
Order By: Relevance
“…The agrarian system is a complex open system that is made of two main sub‐systems and includes cultivated ecosystems and a productive social system (FAO, ; Mazoyer & Roudart, ; Vieira et al ., ; Xie et al ., ; Torres et al ., ) (Figure ). Agricultural systems around the globe continuously change as a result of enlarging trade blocks, globalization and liberalization, the introduction of novel agro‐technologies, changing societal demands, and climate change (Araya et al ., ; Alexander et al ., ; Galati et al ., ; Jlassi et al ., ). Parallel to the liberalization of global markets, the political ambitions devise those policies which aim to improve the sustainability (specially the soil quality) of agricultural systems in terms of economic viability, environmental soundness, and social acceptability, and to enhance the contribution of agricultural systems to the sustainable development of society and global ecosystems at macro level (van Ittersum et al ., ; Smith et al ., ; Keesstra et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…The agrarian system is a complex open system that is made of two main sub‐systems and includes cultivated ecosystems and a productive social system (FAO, ; Mazoyer & Roudart, ; Vieira et al ., ; Xie et al ., ; Torres et al ., ) (Figure ). Agricultural systems around the globe continuously change as a result of enlarging trade blocks, globalization and liberalization, the introduction of novel agro‐technologies, changing societal demands, and climate change (Araya et al ., ; Alexander et al ., ; Galati et al ., ; Jlassi et al ., ). Parallel to the liberalization of global markets, the political ambitions devise those policies which aim to improve the sustainability (specially the soil quality) of agricultural systems in terms of economic viability, environmental soundness, and social acceptability, and to enhance the contribution of agricultural systems to the sustainable development of society and global ecosystems at macro level (van Ittersum et al ., ; Smith et al ., ; Keesstra et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…In fact, the Mediterranean basin is considered a 'hot spot' on a global scale due to: (a) the scarcity of water resources (Giorgi, 2006); (b) climate change (increased temperatures, less snow accumulation and greater atmospheric evaporative demand; Gonzalez-Hidalgo et al, 2016;L opez-Moreno et al, 2008;Polade et al, 2017;Vicente-Serrano et al, 2014); and (c) the significant expansion of the vegetation cover during the last century (Chauchard et al, 2007;García-Ruiz & Lana-Renault, 2011;Sitzia et al, 2010;Vicente-Serrano et al, 2020;Vicente-Serrano & Heredia-Laclaustra, 2004). Water resources are a limitation for economic development in the Mediterranean basin and are an essential factor to satisfy the increasing needs of society, as a consequence of the increase in population, urbanization and living standards , the development of irrigated agriculture (Iglesias et al, 2011;Jlassi et al, 2016) and industrial and tourist activities (Morote et al, 2016;Rico-Amoros et al, 2009). Water resources in Mediterranean regions depend mainly on mountain areas, which act as 'moisture islands' in the middle of drier areas (de Jong et al, 2009;Immerzeel et al, 2020;Viviroli et al, 2011;Viviroli & Weingartner, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The quality and availability of water resources constitute one the most important environmental problems in many countries of the world (i.e., [1]). In the Mediterranean basin, water availability is scarce, with strong seasonal contrasts and most of the flows are produced in mountain rivers [2,3], while water demand is constantly increasing, especially in the lowlands, due to the growth in population and urbanization, the expansion of irrigated areas and greater water consumption of the industrial and tourism sectors [4][5][6]. García-Ruiz et al [7] indicated that Mediterranean countries are among the most under threat worldwide for water stress, due to high inter-annual and seasonal rainfall variability, revegetation processes and a predicted decrease in river flows in the coming decades.…”
Section: Introductionmentioning
confidence: 99%